Neuromodulatory effects of high-definition theta transcranial alternating current stimulation on the parietal cortex: a pilot study of healthy males - Chen, Xixi; Wu, Yuwei; Shi, Xiaolong; Zhou, Zhiqing; Feng, Tingyi; Ren, Meng; Li, Yuanli; Shan, Chunlei (Frontiers in Neuroscience, 2023)
Introduction Transcranial alternating current stimulation (tACS) can regulate brain functions by modulating endogenous brain rhythms. Theta-band neural oscillations are associated with memory function. In particular, theta neural oscillatory power evoked in the parietal cortex is closely related to memory retrieval processes. In this study, the immediate effects of high-definition theta transcranial alternating current stimulation (HDθ-tACS) on the human left parietal cortex were investigated using short-latency afferent inhibition (SAI) and electroencephalography (EEG). Methods Ten subjects participated in this study. We used 6-Hz HD tACS to stimulate the left parietal cortex for 15 min. SAI was calculated, and non-linear dynamic analysis of the EEG was performed to analyze neuronal function after HD θ-tACS. Results The results showed a significant decrease in SAI (p < 0.05), while the left frontoparietal network was reinforced, leading to brain lateralization after HD θ-tACS. During performance of a memory task, F3 signals showed a significant upward trend in approximate entropy following treatment (p < 0.05). There was also a significant decrease in cross-approximate entropy in the C3–C4 and P3–P4 connections following the intervention (p < 0.05) in a resting eyes-open condition and in the memory task condition. Discussion In conclusion, HD θ-tACS could alter cholinergic transmission and cortical excitability between the parietal and motor cortices, as well as reinforcing the frontoparietal network and the left-lateralization phenomenon, which may facilitate memory formation, encoding, and consolidation.